2022
DOI: 10.3390/land11101764
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial-Temporal Evolution of Population in the Yangtze River Delta, China: An Urban Hierarchy Perspective

Abstract: The reason for changes in ranking within urban systems is the subject of much debate. Employing the census data from 1990 to 2020, this paper investigates population dynamics across urban hierarchies and its influencing factors in the Yangtze River Delta. The results reveal an upward pattern of population dynamics and show that the advantages of high-ranking cities in population gathering are obvious, though they have declined recently. Based on a framework of urban amenity and the ridge regression model, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…This study analyzes the changes in regional population distribution from the perspective of population migration. Existing studies have shown that population migration is influenced by various factors such as natural, economic, political, and cultural factors [8,11]. In particular, physical geographic conditions, economic and social development, and policy factors shape the spatial patterns of population distribution and its changes.…”
Section: Multiple Linear Regression Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…This study analyzes the changes in regional population distribution from the perspective of population migration. Existing studies have shown that population migration is influenced by various factors such as natural, economic, political, and cultural factors [8,11]. In particular, physical geographic conditions, economic and social development, and policy factors shape the spatial patterns of population distribution and its changes.…”
Section: Multiple Linear Regression Modelmentioning
confidence: 99%
“…The pattern of population dynamics among cities is closely related to population migration. Population migration generally follows two basic paths, namely upward and downward along the urban hierarchy, both of which have important effects on the inter-city population distribution dynamics [11][12][13]. For example, upward population migration brings about an increase in population in large cities and a decrease in population for small and medium-sized cities (SMSC), resulting in an uneven inter-city population distribution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations